GAMBARAN KESEHATAN REPRODUKSI PENYAPU JALANAN PEREMPUAN DI KOTA BALIKPAPAN TAHUN 2016 - Eli Rahmawati (Politeknik Kesehatan Kementerian Kesehatan Kalimantan Timur, 2017)
Abstract The street sweeper is a group of high-risk workers, vulnerable to accidents and illness. One of them is the infected reproductive organs due to the use of public toilets. Preliminary study of most women's street swabs CHAPTER / BAK while working in public toilets, workers do not get maternity leave and holidays. The purpose of this research is to know the characteristics and description of reproductive health of female street sweeper covering the way to keep the reproduction organ clean, the use of public toilet, the pattern of working hours, rest, maternity leave and the use of PPE. Research design mixed method. The population is a street contract female street sweeper DKPP Balikpapan amounted to 260 people. Accumental sampling sampling technique with a sample size of 100 people. Characteristics of respondents in most ages> 40 years (64%), elementary education (40%), Islam (99%) and longest working time> 10 years. The majority of respondents still get menstruation (63%), highest parity of 2-4 people (66%), majority do not use contraception (66%), whiteness 27%, have disease history 26% and as much as 38% choose office for CHAPTER / BAK While working. Personal protective equipment is well equipped by DKPP. Maternity leave is on average 1 month, no annual leave, but allowed to take leave if necessary. The pattern of working hours and breaks is divided into two shifts ie morning shift starting at 06.00 s.d 12.00 noon and at 12.00 s.d 18.00 afternoon. The average break ranges from 1-2 hours. Suggested research results are followed up for community service on knowledge of how to maintain reproductive organs, the government pay more attention to facilities and facilities kespro, the right of workers leave and improve knowledge of reproductive health of street sweepers from various sources. Keywords: image of reproductive health, female street sweeper Abstrak Petugas penyapu jalanan merupakan kelompok pekerja berisiko tinggi, rentan kecelakaan dan terserang penyakit. Salah satunyaadalah organ reproduksi yang terinfeksi karena penggunaan toilet umum. Hasil study pendahuluan sebagian besar penyapu jalanan perempuan BAB/BAK saat bekerja di toilet umum, pekerja tidak mendapatkan cuti bersalin dan libur. Tujuan penelitian adalah diketahuinya karakteristik dan gambaran kesehatan reproduksi penyapu jalanan perempuan meliputi cara menjaga kebersihan organ reproduksi, penggunaan toilet umum, pola jam kerja, istirahat, cuti bersalin dan penggunaan APD. Rancangan penelitian mixed method. Populasi adalah tenaga kontrak penyapu jalanan perempuan DKPP kota Balikpapan berjumlah 260 orang. Teknik sampling accindental sampling dengan besar sampel 100 orang. Karakteristik responden usia terbanyak > 40 tahun (64%), pendidikan SD (40%), agama Islam (99%) dan waktu bekerja terlama > 10 tahun. Mayoritas responden masih mendapatkan haid (63%), paritas tertinggi 2-4 orang (66%), mayoritas tidak menggunakan kontrasepsi (66%), mengalami keputihan 27%, memiliki riwayat penyakit 26% dan sebanyak 38% memilih perkantoran untuk BAB/BAK saat bekerja. Alat pelindung diri sudah dilengkapi dengan baik oleh DKPP. Cuti bersalin ada rata-rata 1 bulan, tidak ada cuti tahunan, namun diperbolehkan ajukan cuti jika ada keperluan. Pola jam kerja &istirahat dibagi menjadi dua shift yaitu shift pagi dimulai jam 06.00 s.d 12.00 siang dan pukul 12.00 s.d 18.00 sore. Istirahat rata-rata berkisar antara 1-2 jam. Disarankan hasil penelitian ditindaklanjuti untuk pengabdian masyarakat tentang pengetahuan cara menjaga organ reproduksi, pemerintah lebih memperhatikan fasilitas dan sarana kespro, hak cuti pekerja dan meningkatkan pengetahuan kesehatan reproduksi para penyapu jalanan dari berbagai sumber. Kata Kunci: gambaran kesehatan reproduksi, penyapu jalanan perempuan